Block copolymer molecular design to address practical limitations to recycling polyolefin blends - Shuquan Cui; Daun Jeong; Yukai Shi; Nusrat Jahan; Timothy P. Lodge; Frank S. Bates; Christopher J. Ellison (Proceedings of the National Academy of Sciences, 2025)
Plastics offer innumerable societal benefits but simultaneously contribute to persistent environmental pollution, dominated by polyethylene (PE) and isotactic polypropylene ( i PP). Melt blending and reformulating postconsumer PE and i PP into useful materials presents a promising recycling approach. However, such repurposed plastics are generally mechanically inferior due to an inability to efficiently separate polyolefins in mixed waste streams; phase separation of PE and i PP results in brittleness as a consequence of poor interfacial strength. Recently, we demonstrated that a small amount (1 wt%) of a poly(ethylene)- block -poly(ethyl ethylene- ran -ethylene)- block -poly(ethylene) (EXE) triblock copolymer, synthesized by low-cost anionic polymerization of 1,3-butadiene followed by solution hydrogenation, restores tensile toughness to levels equivalent to virgin polyolefins. Unfortunately, low-temperature solvent insolubility of EXE, driven by crystallization of the E blocks containing 1.5 ethyl branches per 100 backbone repeat units (EB), presents a challenge for industrial hydrogenation. Comparable toughness (ca. > 400% strain at break) was achieved in the present work with 1.5 ≤ EB ≤ 6.5, accompanied by reduced EXE crystallinity and dissolution in cyclohexane down to room temperature at the highest EB content. This remarkable toughening behavior is attributed to a synergy between chain entanglements between the E end blocks and semicrystalline PE homopolymer and formation of E block “crystal nodules” that prevent chain pullout, along with topological constraints between the X loops and semicrystalline i PP. Our findings overcome barriers to commercial production of EXE with existing industrial facilities, providing a cost-effective strategy for recycling PE and i PP.